Determinant of Coparenting Behavior in Intact Family: a Literature Review - Dewi Ilma Antawati; Wiwin Hendriani; Duta Nurdibyanandaru (Universitas Ahmad Dahlan, 2020)
Abstract Research on coparenting has been quite developed in the last four decades. In Indonesia, research related to coparenting still deals with father involvement in child care. While in other countries various coparenting behavior models have been developed in various context. This systematic review examines the empirical literature in the last ten years focusing on the determinants of coparenting behavior in intact family. Although at the beginning of its development coparenting research was carried out on divorced couples, this review examined the determinants of coparenting behavior in married couples. From several databases, the results show that determinants of coparenting behavior are involving of parental characteristics, child characteristics, marital relationships, and intervention program. It is expected that the results of this study can become a reference for conducting researchers on coparenting behavior especially in Indonesian family.Keywords: parenting, coparenting, intact family